'The only good thing that happened at school': colonising narratives of sport in the Indian School Bulletin. Issue 2 (September 2017) - Forsyth, Janice; Heine, Michael
Abstract : This article examines how sport, recreation, and physical activity practices were represented in the Indian School Bulletin, a newsletter that was published by the Indian Affairs Branch from 1946 to 1957 to provide guidance and instruction for the teachers in its residential school system. During this time, the Branch made organised, competitive physical activities a primary site for the advancement of its assimilationist programmes and used the Bulletin to communicate its policy priorities to the teachers, who were to foster involvement in such activities whenever possible. Findings from this article acknowledge the colonising impacts of sports and recreation while highlighting the complexities stemming from those impacts, in particular, narratives about the 'positives' of sports and residential schooling.